Estudio de la calidad de la pasta de cacao (Theobroma cacao) a partir de dos tipos de clones cultivados en la provincia Bolívar - Infante Olalla, Kleber Alexis (2025)
This investigative work was carried out with the purpose of studying the quality of cocoa paste (Theobroma cacao) made from two types of clones grown in the Bolívar Province, Las Naves canton. It is important to emphasize that Theobroma cacao is the scientific name of fine aroma cocoa. Ecuador is one of the countries that cultivates, produces and exports this product, such is the case of the Province of Bolívar, which is privileged with its cultivation; However, due to the lack of knowledge of the value chain of fine aroma cocoa, among the main factors, low productivity of agricultural and artisanal activities is generated along with the lack of technical training of producers, loss of product and profitability. In this study, the cocoa varieties INIAP-EETP-800 and INIAP-EETP-801 were shown to originate from clones and their physicochemical and microbiological composition was analyzed through methods based on INEN and AOAC standards; Also, a sensory analysis was demonstrated through an evaluation sheet of the cocoa paste. Their studies determine that the paste of the cocoa varieties under study are safe products since they comply with the requirements established by the NTE INEN 623:2006 standard on the requirements of cocoa paste, which establishes that the moisture content must be lower at 8%, whose results were for EETP-800 which corresponds to 1.04% and for EETP-801 which corresponds to 3.71%; For its part, the fat content was between 47% - 60% in accordance with what is established by the AOAC 2003:06 standard and the results were EETP-800 with 52.18% and EETP-801 with 52.09%; and ash less than 5%, EETP-800 being 0.07% and EETP-801 being 0.06%, as well as NTE INEN 621:2010 of the chocolate requirements; to produce various products from both the raw material and the cocoa paste and make their diversity known.